2015
DOI: 10.1002/pros.23052
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation screening of primary prostate tumors identifies SRD5A2 and CYP11A1 as candidate markers for assessing risk of biochemical recurrence

Abstract: Overall, increased DNA methylation of SRD5A2 and CYP11A1 related to androgen biosynthesis functions may play a role in BCR after patients' RP. The correlation between aberrant cfDNA methylation and detectable PSA in post-RP further suggests their utility as predictive markers for PCa recurrence. .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…Similar associations have also been reported in previous studies which suggested that RASSF1 , RARB2 , and/or GSTP1 ctDNA methylation may predict the stage and grade of localized PC (Sunami et al ., ). Furthermore, it has been proposed that GSTP1 , SRD5A2 , CYPIIAI , and PCDH17 ctDNA methylation may predict BCR risk after RP (Bastian et al ., ; Horning et al ., ; Lin et al ., ). Conceivably, the ctDNA methylation level in a liquid biopsy may therefore help assess PC aggressiveness at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Similar associations have also been reported in previous studies which suggested that RASSF1 , RARB2 , and/or GSTP1 ctDNA methylation may predict the stage and grade of localized PC (Sunami et al ., ). Furthermore, it has been proposed that GSTP1 , SRD5A2 , CYPIIAI , and PCDH17 ctDNA methylation may predict BCR risk after RP (Bastian et al ., ; Horning et al ., ; Lin et al ., ). Conceivably, the ctDNA methylation level in a liquid biopsy may therefore help assess PC aggressiveness at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Lots of researches have reported the wide range of DNA concentrations in the plasma of PCa and BPH patients [ 35 , 36 ]. As the analytic methods for the detection of hypermethylated cfDNA in cancer patients are well-established [ 37 ], thus, in the qualitative analysis subgroup, we mainly focused on the detection of cfDNA methylation. Wu et al had conducted a meta-analysis and concluded that GSTP1 promoter methylation measured in plasma, serum, or urine samples, in combination with PSA screening, would significantly enhance the diagnosis accuracy for PCa [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, other variable DNA methylation alterations in neoplastic tissue samples have been also associated with the prediction of PSA recurrence after RP [10,17,18,19,20,21,22,23,24]. These studies have identified new potential tumor markers including methylation of PITX2 , HOXD3 , APC , TGFβ2 , RASSF1A , ANEP , PCDH10 , ZNF132 , TDRD1 , AOX1 , C1orf114 , GAS6 , HAPLN3 , KLF8 , MOB3B , CCND2 , PTGS2 , RARB , SRD5A2 and CYP11A1 , thus emerging as new predictors of BCR particularly in high-risk clinically localized disease.…”
Section: Discussionmentioning
confidence: 99%